HAK ASASI MANUSIA DALAM SASTRA LISAN MASYARAKAT BUGIS (PERSPEKTIF HERMENUTIKA) - ., Amaluddin (Universitas Muhammadiyah Surakarta, 2012)
Oral Literature of Bugis Society is the culture heritage in Bugis society. As a cultural heritage, Oral Literature of Bugis Society used as a medium of artistic expression to convey a variety of things about life of Bugis people, including the very fundamental humanity messages of the importance of human rights upholding. Oral Literature of Bugis also serves as a popular entertainment medium for society. The focus in this study is the use of diction in Oral Literature of Bugis Society. This study is qualitative research using hermeneutical theory design. Based on this research, many found the use of diction such as asipakataungÃªng, adeleâ, sipakatau, assicocokÃªng na asalÃªwangÃªng, alÃªbbirÃªng, assimÃªllÃªrÃªng/ siakkamasÃªang which has a very deep meaning to represent the life of the Bugis society.